Fungal nanoscale metal carbonates and production of electrochemical materials. Issue 5 (17th July 2017) - Li, Qianwei; Gadd, Geoffrey Michael
Abstract : Fungal biomineralization of carbonates results in metal removal from solution or immobilization within a solid matrix. Such a system provides a promising method for removal of toxic or valuable metals from solution, such as Co, Ni, and La, with some carbonates being of nanoscale dimensions. A fungal Mn carbonate biomineralization process can be applied for the synthesis of novel electrochemical materials.